Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Pos Indonesia Cabang Karawang - Felix Oktavianus Wijaya; Syifa Pramudita Faddila (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
Motivation is one of the things that influence human behavior, motivation is also known as a driving force for desires, supporters or needs that can make a person excited and motivated to fulfill their own motivation, so that they can act and act according to certain ways that will lead to the desired direction. optimal. This study aims to determine how the influence of work motivation on the performance of employees of PT Pos Indonesia, Karawang Branch. The research location was at Pt.Pos Indonesia Karawang branch, the respondents were employees of PT. Pos Indonesia Karawang branch. The population is 94 people, and the sample is 94 people. The sampling technique used in this study is the Saturated Sampling Technique. Furthermore, data was collected through interviews in a structured Likert scale and distributed using the Google form. Heteroscedasticity Test and Data Normality Test were carried out on the questionnaire on samples. The results showed that motivation had a significant effect on performance.